IMPROVING STUDENTS’ SPEAKNG SKILL IN THE ASPECT OF GRAMMAR AND VOCABULARY ABOUT DESCRIBING ANIMALS BY USING CUE CARDS MEDIA - Putri, Dewi Sartika; Sada, Clarry (FKIP - Universitas Tanjungpura, 2021)
This research aimed at improving the students’ speaking skill at grade VII of SMP Islamiyah Pontianak in the academic year of 2019/2020 through cue cards media. This classroom action research was conducted in three cycles; on November 14th, 21st and 28th respectively. It involved 22 seventh grader students as well as the English teacher as the collaborator. The data were taken from the observation, field notes and speaking task. The data of speaking was obtained by speaking task which was assessed through scoring rubric. The result showed that students’ problems in grammar and vocabulary had been solved by using Cue Cards media. The most interesting part of this research was, the cue cards could break the ice among the students as there are pictures and questions which stimulate students’ prior knowledge and could be used as handy clues for them during the learning process. Furthermore, the students’ speaking improved constantly from cycle 1 (the highest score was 48, 3 students got score 48), cycle 2 (the highest score was 64, 2 students got score 64) and cycle 3 (the highest score was 84, 6 students had not achieved the minimum score which is 75). Not only their individual speaking achievement got improved, but also their interest in learning. It was shown by the students’ enthusiasm to pay attention and involve actively in doing every activity during teaching and learning process by using cue cards. Keywords: Speaking, Cue Cards, Media